2010
DOI: 10.1007/s11136-010-9690-9
|View full text |Cite
|
Sign up to set email alerts
|

Application of the health assessment questionnaire disability index to various rheumatic diseases

Abstract: PurposeTo investigate whether the Stanford Health Assessment Questionnaire Disability Index (HAQ-DI) can serve as a generic instrument for measuring disability across different rheumatic diseases and to propose a scoring method based on item response theory (IRT) modeling to support this goal.MethodsThe HAQ-DI was administered to a cross-sectional sample of patients with confirmed rheumatoid arthritis (n = 619), osteoarthritis (n = 125), or gout (n = 102). The results were analyzed using the generalized partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 18 publications
0
42
0
1
Order By: Relevance
“…Therefore, an ES Ͼ0.10 was considered to indicate significant DIF across countries, irrespective of the statistical significance of the LM tests. This cutoff point has previously been used in research related to the original HAQ DI, which has the same response format as the HAQ-II (8). Initially, the much larger US sample dominated the concurrent item parameter estimates and spuriously inflated the deviation of observed Dutch scores from the model expectations.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, an ES Ͼ0.10 was considered to indicate significant DIF across countries, irrespective of the statistical significance of the LM tests. This cutoff point has previously been used in research related to the original HAQ DI, which has the same response format as the HAQ-II (8). Initially, the much larger US sample dominated the concurrent item parameter estimates and spuriously inflated the deviation of observed Dutch scores from the model expectations.…”
Section: Methodsmentioning
confidence: 99%
“…Both the 28-and 38-joint counts of tenderness and swelling had to fit the GPCM before the contribution of the forefoot joints could be analyzed. This fit was analyzed with Lagrange Multiplier Q1 tests (15), where absolute effect sizes of Ͻ0.10 were seen as an indication of good item-model fit (16,17).…”
Section: Methodsmentioning
confidence: 99%
“…However, the relationship between PF scores and the latent PF construct may differ between patients with different cultural backgrounds or between patients with different diseases. For example, previous research has shown that HAQ DI items function differently between patients with gout, osteoarthritis, and RA (7). Therefore, the generalizability of a crosswalk needs to be tested before it can be used in a new setting.…”
Section: Introductionmentioning
confidence: 99%